Tourism Transition and Green Economy: Inspire or Prevent People's Income in The Covid-19 Shock? - Normasyhuri, Khavid; Noviarita, Heni; Kurniawan, Muhammad; Nurmalia, Gustika (MATRIK: JURNAL MANAJEMEN, STRATEGI BISNIS, DAN KEWIRAUSAHAAN, 2023)
The COVID-19 pandemic, which resulted in the destruction of all existing regulatory systems, faced many obstacles, especially in the field of tourism, including tourism villages. The Green Economy concept is expected to be a way out and a bridge between people's income growth, social justice and environmental friendliness. This research was conducted with the aim of analyzing the green economy transition in tourism, especially tourist villages, whether it is able to provide inspiration or actually prevent an increase in people's income in conditions of the COVID-19 shock. This study develops a model to see the relationship between green economy and people's income. Quantitative in this study used SmartPLS 3.0 in analyzing data obtained from 600 respondents through the observation stage and a list of questions given. The research was carried out in tourist villages in West Java and Lampung Provinces carried out in the context of COVID-19. This study found thatthe transition of a tourist village with the concept of green economy has a strong influence in increasing the income of rural tourism communities in conditions of the COVID-19 shock. This is because, tourist villages with the concept of green economy are able to create a special attraction for tourists the design of a tourist village is carried out in accordance with the surrounding natural conditions and the habits of life of the people so that the tourist village is eyed by many foreign tourists as well as local tourists and when tourists come, of course there will be an economic turnover in the village and implications for the local community economically, socio-culturally and the surrounding environment.